2014
DOI: 10.1021/nn404346v
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled All-Conjugated Block Copolymer as an Effective Hole Conductor for Solid-State Dye-Sensitized Solar Cells

Abstract: An all-conjugated diblock copolymer, poly(2,5-dihexyloxy-p-phenylene)-b-poly(3-hexylthiophene) (PPP-b-P3HT), was synthesized and applied as a hole transport material (HTM) for the fabrication of solid-state dye-sensitized solar cells (ss-DSCs). This copolymer is characterized by an enhanced crystallinity, enabling its P3HT component to self-organize into interpenetrated and long-range-ordered crystalline fibrils upon spin-drying and ultimately endowing itself to have a faster hole mobility than that of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…[43, 44] To gain insight into the interfacial resistance of the samples, EIS measurements were carried out at open-circuit voltages and in the dark. The Nyquist plots of all the samples are shown in Fig 8.…”
Section: Resultsmentioning
confidence: 99%
“…[43, 44] To gain insight into the interfacial resistance of the samples, EIS measurements were carried out at open-circuit voltages and in the dark. The Nyquist plots of all the samples are shown in Fig 8.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al investigated the properties of a pre-polymerized block copolymer of poly(3-hexylthiophene) and poly(2,5-dihexy- p -phenylene), and found that a PPP- b -P3HT-based solar cell achieved a V OC of 810 mV, J SC of 8.81 mA cm −2 , FF of 65% and PCE of 4.65%. 476 …”
Section: Methodsmentioning
confidence: 99%
“…475 Wang et al investigated the properties of a pre-polymerized block copolymer of poly(3-hexylthiophene) and poly(2,5-dihexyp-phenylene), and found that a PPP-b-P3HT-based solar cell achieved a V OC of 810 mV, J SC of 8.81 mA cm À2 , FF of 65% and PCE of 4.65%. 476 Liu et al investigated the performance of P3HT with two different dyes. When sensitised with BzTCA, solar cells achieved a V OC of 880 mV, J SC of 8.22 mA cm À2 , FF of 44% and PCE of 3.21%, demonstrating that organic dyes are better suited to operate with polymeric HTMs.…”
Section: Polymeric Hole Transporting Materialsmentioning
confidence: 99%
“…Wang and coworkers explored the properties of a prepolymerized block copolymer of poly(2,5-dihexyloxy-p-phenylene), PPP and poly(3-hexylthiophene), P3HT. 268 The PPP block helped the PPP-b-P3HT copolymer to self-organize in crystalline domains, which increased the hole mobility of the copolymer significantly (8.5 Â 10 À4 cm 2 V À1 s À1 ) compared to the P3HT homopolymer (1.9 Â 10 À4 cm 2 V À1 s À1 ) and, as the authors claimed, provided a more intimate contact with the CYC-B11 dye. The pore filling proved to be similar for both copolymer and P3HT but, thanks to the higher hole mobility and better contact with the dye, the PPP-b-P3TH-based solar cell achieved a V OC of 810 mV, J SC of 8.81 mA cm À2 , FF of 0.65 and PCE of 4.65%; while those employing P3HT could only display a V OC of 750 mV, J SC of 7.71 mA cm À2 , FF of 0.61 and PCE of 3.53%.…”
Section: Organic Hole Transporting Materialsmentioning
confidence: 91%